Stabilizing currency and preserving economic sovereignty using the Grondona system - Collins, Patrick Quentin, 1952- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book describes how implementing Grondona's system could help individual countries to independently improve their economic stability, while creating a growing network of currencies between which the exchange-rates will become increasingly stable"--